Unveiling the Aesthetics of Glass Product Innovation: A Journey into the Extraction and Application of Cultural Heritage Elements - Liu, Qingfeng; Nurul 'Ayn Ahmad Sayuti,; Hong Chen, (Advances in Humanities and Contemporary Studies, 2024)
Nowadays, China's cultural creative industry is booming. However, glass product design in China is heavily influenced by Western culture. Adding more Chinese cultural elements to the appearance innovation of glass products can make glass products more in line with local aesthetic standards and increase cultural identity. This research adopts the method of qualitative research to explore the method for incorporating cultural heritage elements into glass products. First, 100 glass products with cultural heritage elements in today's market are investigated and collected. Then, the ten most representative glass products are identified by SETIG factor analysis for case analysis and analyzed according to the three main aesthetic characteristics of color, shape, and decoration. It is found that the visual elements of cultural heritage can be extracted from the three aspects of shape, color, and decoration and can be transformed by the method of composition. The further method of this research can be through the investigation of the symbolic meaning of visual elements, and these semantic variable values can improve the added value of glass products.